Experimental comparative study between storytelling and storydoing in Facebook advertising - Antonio Rodríguez-Ríos; Patrícia Lázaro-Pernias (Communication & Society (Formerly Comunicación y Sociedad))
In 2015, the United Nations established a global framework to address the challenges concerning the economic, social and environmental development of the planet. In this context, brands align themselves with the Sustainable Development Goals (SDGs) to contribute to their well-being and to that of society, and to enhance their reputation through honest and transparent communication (Lazo & Patiño, 2016; Bandyopadhyay & Ray, 2020). In this framework, this research aims to measure the effectiveness of storydoing understood as a strategic communication model refined from storytelling. To this end, a sample of 425 parents of different nationalities was exposed to a survey in which they were asked about the different dimensions that make up the engagement construct and about the consumption intention generated by each of the stimuli hosted on Facebook. These are two creativities that belong to the storydoing advertising campaign of Power Xoc, a soluble cocoa brand created ad hoc that provides society with a series of tools to fight against bullying. The results show that the storydoing piece generates more engagement than storytelling, a phenomenon that explains why Facebook users have the intention to buy the advertised product. Consequently, this work contributes to empirically ground the theory of social exchange through the impact of advertising based on narrative patterns in a society that responds against social injustices.